(untitled) (CIPEEX, 2025)
The university outreach project integrates teaching, health services, and the community, strengthening promotion, prevention, and ongoing care. Eye health, often neglected in aging, plays a central role in the quality of life and functional autonomy of older adults, with visual impairment being a risk factor for falls, social isolation, and cognitive decline. This paper reports on the experience of a university outreach project that conducts visual acuity tests on community-dwelling seniors, aiming to promote eye health and strengthen integrated care. The activity takes place weekly in senior living units, using the adapted Snellen chart. After administering the test, medical students provide educational guidance on eye hygiene, adequate lighting in the home, proper use of glasses, and prevention of eye diseases. When students identify visual changes, these seniors are advised to seek specialized ophthalmological evaluation so that appropriate health measures can be taken. The experience demonstrates broad receptiveness among the seniors, who demonstrate an interest in understanding the importance of vision for maintaining independence and well-being. The initiative also brings the university and the community closer together, encouraging humane and preventive practices among the students involved. The conclusion is that visual acuity testing, as an outreach activity, is an effective strategy for early detection of visual changes, promoting eye health, and strengthening comprehensive care for the elderly population.